OPTIMAL ORIENTATION OF FARMS DEPENDING ON MANPOWER AND BUILDING FACILITIES IN CATTLE BREEDING - Bastajić, Ljubomir; Veljković, Biljana (Economics of Agriculture, 2006)
An influence of available manpower and building facilities in cattle breeding, on family farm optimal production orientation, were analyzed in the study. Insufficient available manpower and building facilities in cattle breeding present limited factors in family farm business In order to select an optimal production orientation, modeling method was used. Four family farm models were made, that differ mutually by used manpower and size of existing building facilities in cattle breeding. Family farm models were solved by simplex method of linear programming with the help of computer and by using program package Solver in Excel. For the optimal criteria function maximizing of cover margins was used.